Developing Reading Skills Using Sight Word Reading Strategy through Interactive Mobile Game-Based Learning for Dyslexic Children - Noor Hazlini, Borhan; Hamizan, Sharbini; Chiu, Po Chan; Azlina, Ahmadi Julaihi (2015)
Reading skill is crucial in our daily activities. On the other hand, there are some people who experience difficulties in reading. This is due to the way they see things are different than normal people. This learning disability is known as dyslexia. The symptoms started from young. Children with dyslexia use allof their senses to interact with their surroundings. They are easily attracted to pictures rather than words and are highly imaginative. In this project, a mobile application to help children with dyslexia to develop reading skills is proposed. This paperwill discuss about the development of the mobile application. The methodology used in this project will be discussed along with the implementation and testing. The results have shown that respondents gave positive feedbacks prove that the application is effective in developing reading and spelling among dyslexic children. Lastly, limitations, future works and conclusion of the overall project will be discussed. The mobile application is named as “Mr Read”.